A Sweet Potion to Put Embryonic Stem Cells to Sleep. (2009) - Deb, Kaushik D.
Abstract : Human embryonic stem cells (hESCs) are rapidly revolutionizing the areas of drug screening and therapy. In view of their applications and high operational costs at global multicentric setups, the ability to store and transport hESCs and derivatives under ambient temperatures, and their cryopreservation without compromising the stemness, function, and viability, is becoming imperative. Here we discuss the need for a natural cryoprotectant and biopreservative with a potential to improve cryopreservation, ambient temperature storage, and shipping of hESCs and derivatives. Trehalose, a naturally occurring disaccharide with therapeutic properties, protects the integrity of cells against desiccation, dehydration, and extreme heat or cold, and has been successfully tested for some somatic stem cell types. However, the biggest setback is the inability of mammalian cells to internalize trehalose. Here we review the methods being developed at different laboratories to facilitate its intercellular transport and advocate the need for similar advances in hESCs.